High Glucose Aggravates the Detrimental Effects of Pancreatic Stellate Cells on Beta-Cell Function - Min Zha; Wei Xu; Qing Zhai; Fengfei Li; Bijun Chen; Zilin Sun (International Journal of Endocrinology)
Background and Aims. We here assess the effects of PSCs on β-cell function and apoptosis in vivo and in vitro. Materials and Methods. PSCs were transplanted into Wistar and Goto-Kakizaki (GK) rats. Sixteen weeks after transplantation, β-cell function, apoptosis, and islet fibrosis were assessed. In vitro the effects of PSCs conditioned medium (PSCs-CM) and/or high concentration of glucose on INS-1 cell function was assessed by measuring insulin secretion, INS-1 cell survival, apoptosis, and endoplasmic reticulum stress (ER stress) associated CHOP expression. Results. PSCs transplantation exacerbated the impaired β-cell function in GK rats, but had no significant effects in Wistar rats. In vitro, PSCs-CM caused impaired INS-1 cell viability and insulin secretion and increased apoptosis, which were more pronounced in the presence of high glucose. Conclusion. Our study demonstrates that PSCs induce β-cell failure in vitro and in vivo.